THE MANAGEMENT OF SOLID WASTE FROM HEALTH SERVICES IN BRAZIL - Claudia Rodrigues da Silva, Ana (Health and Society, 2023)
INTRODUCTION: The global concern regarding solid waste has increased due to the growth of production, inadequate management and the lack of final disposal areas. Some authors claim that the multiplication of solid urban waste is directly connected with an increase in population and the indiscriminate use of natural resources, causing significant environmental and socioeconomic impacts. GENERAL OBJECTIVE: To understand the factors involved in the management of solid waste in health services. METHOD: This research was based on the analysis of the literature already published in the form of scientific articles made available on the internet databases: Scielo and LILACS, with publications in the last 10 years (2010 to 2020). RESULTS: Currently the main resolutions in force on health service waste (RSS) are: Resolution of the National Environment Council (CONAMA) nº 385/2005 and Resolution of the Collegiate Board (RDC) of ANVISA nº 222 / 2018. Brazil’s challenges in the management of SSR are: the difficulty in adequate segregation, the precarious treatment and final disposal of this waste in the country - in which only part is deposited in controlled landfills. CONCLUSION: Due to the large amount and variety of waste generated in hospitals, it is necessary that segregation and the other stages of the management of RSSS occur properly, as there are several risks involved: biological, chemical and occupational. It is possible to point out three guiding principles for waste management: avoid the generation of waste, segregate and recycle. These principles must be incorporated into the establishment’s RSS Management Plan.